Don't let it get you down : essays on race, gender, and the body - Nolan, Savala (Simon & Schuster, 2021)
"An incisive and vulnerable yet powerful and provocative collection of essays, Savala offers poignant reflections on living between society's most charged, politicized, and intractably polar spaces: between black and white, between rich and poor, between thin and fat - as a woman. The daughter of an Afro-Latinx father and a white mother, Savala's light complexion has always contrast her kinky hair and broad nose to embody what old folks used to call "a whole lot of yellow wasted." With her mother's beckoning, she began her first diet at the age of three and has been nearly skeletal and truly fat, multiple times. She has lived in poverty and had an elite education, with regular access to wealth and privilege. She has been in the in between. It is these liminal spaces - the living in the in-between of race, class and body type that gives the essays in Nearly, Not Quite their strikingly clear and refreshing point of view on the defining tension points in our culture. Each of the twelve essays, that comprises this collection are rife with unforgettable and insightful anecdotes, and are as humorous and as full of Savala's appetites as they are of anxieties. The result is a lyrical and magnetic read. In "On Dating White Guys While Me," Savala realizes her early romantic pursuits of rich, preppy white guys wasn't about preference, but about self-erasure. In "Don't Let it Get You Down" we traverse the beauty and pain of being Black in America as men of color face police brutality and "large Black females" are ignored in hospital waiting rooms. Savala offers an angle to inequities that is as deft as it is lyrical. In "Bad Education" we mine how women learn to internalize violence and rage in hopes of truly having power. And in "To Wit and Also" we meet Filliss, Peggy, and Grace the enslaved women owned by her ancestors, reckoning with how America's original sin lives intimately within our stories. Over and over again, Savala reminds readers that our true identities are often most authentically lived not in the black and white in the grey, in the in-between. Perfect for fans of Heavy by Kiese Laymon and Bad Feminist by Roxane Gay, this book delivers a fresh perspective on race, class, bodies, and gender, that is both an entertaining and engaging addition to the ongoing social and cultural conversation"--